2023
DOI: 10.3390/microorganisms11051198
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Lysine Residue of Pneumococcal Triosephosphate Isomerase Contributes to Its Binding to Host Plasminogen

Abstract: The main causative agent of pneumonia, Streptococcus pneumoniae, is also responsible for invasive diseases. S. pneumoniae recruits human plasminogen for the invasion and colonization of host tissues. We previously discovered that S. pneumoniae triosephosphate isomerase (TpiA), an enzyme involved in intracellular metabolism that is essential for survival, is released extracellularly to bind human plasminogen and facilitate its activation. Epsilon-aminocaproic acid, a lysine analogue, inhibits this binding, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Among the proteins expressed by S. pneumoniae, Eno [28][29][30][31][32][33][34], GAPDH [35], cholinebinding protein E (CbpE) [45], plasmin-and fibronectin-binding protein A (PfbA) [46], plasminogen-and fibronectin-binding protein B (PfbB) [47], endopeptidase O (PepO) [48], Tuf [36], phosphoglycerate kinase [49], pneumococcal surface protein C (PspC) [50], TpiA [15,51], ClpC [17], and UvrC [17] bind plasminogen. A few of these, including Eno [28], CbpE [45], PepO [48], Tuf [36], and TpiA [15], use lysine residues in the protein molecule to bind to plasminogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the proteins expressed by S. pneumoniae, Eno [28][29][30][31][32][33][34], GAPDH [35], cholinebinding protein E (CbpE) [45], plasmin-and fibronectin-binding protein A (PfbA) [46], plasminogen-and fibronectin-binding protein B (PfbB) [47], endopeptidase O (PepO) [48], Tuf [36], phosphoglycerate kinase [49], pneumococcal surface protein C (PspC) [50], TpiA [15,51], ClpC [17], and UvrC [17] bind plasminogen. A few of these, including Eno [28], CbpE [45], PepO [48], Tuf [36], and TpiA [15], use lysine residues in the protein molecule to bind to plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“…A few of these, including Eno [28], CbpE [45], PepO [48], Tuf [36], and TpiA [15], use lysine residues in the protein molecule to bind to plasminogen. A recent study on TpiA reported that the plasminogen binding site was located at the C-terminus [51]. In Eno, which has been studied the most, the binding site for plasminogen has been identified as two C-terminal lysine residues and the nine-amino acid motif FYDKERKVY, located at positions 248-256 [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation